A new genus with a new species of cricket from mid-Cretaceous Burmese Kachin amber (Orthoptera: Trigonidiidae). (October 2022) - Liu, Yi-Jiao; Yu, Zhe-Yuan; He, Zhu-Qing
Abstract: A new genus and a new species of Trigonidiidae, Curvospurus huzhengkun gen. et sp. nov., is described on the basis of a cricket specimen in mid-Cretaceous Burmese amber. Its attribution to Trigonidiidae can be inferred by small body size, strong setae over the whole body (especially in the head and pronotum), hind tibia with spurs but without spines, hind basitarsomere not serrulated. However, the features of four apical spurs on fore tibia and two veins across harp on forewing distinguishes this genus from Trigonidiinae or Nemobiinae. The new species has novel morphological features such as two curved dorsal inner spurs on hind tibia, which probably indicates the original of female chewing tibial spur behavior or competition between males.